An Exploratory Study of Video Game Pricing in the Southeast Asian Market - Wibowo, Tony; Sandriawan, Elfan; Eryc (Universitas Multimedia Nusantara, 2025)
This exploratory study examines optimal video game pricing within the Southeast Asian market from the perspective of gamers. Employing a two-phase quantitative analysis of 405 respondents across six nations—Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam—the study identifies a consistent psychological pricing framework. Key findings reveal two stable price thresholds: a normative expectation of approximately USD 20 for indie titles and an upper limit of USD 40–60 for premium AAA games. The research confirms a significant market transition from price sensitivity to value sensitivity, where developer reputation and production quality directly influence price acceptance. Furthermore, the study substantiates the emergence of a